Perancangan User Experience Aplikasi Platfrom Komunitas Sosial Animal Welfare di Kota Malang menggunakan Metode Human Centered Design - Yoga Sadewa; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
SCD (Stray Cat Defender) is one of the animal welfare communities that cares about the condition of stray cats in Malang City. SCD has several community activity programs, namely Rescuing, Animal Care, Sterilization, Adoption, and Campaign. In the adoption process is that the community can only share adoption offers provided by netizens for 24 hours, so the information provided does not last longer and the adoption status of the offered cats cannot be monitored. In addition, similar problems also occur when netizens provide information about missing cats. The Human Centered Design (HCD) approach was used in this research to identify the right solutions for the problems in the community. The HCD stages include user context analysis, user needs analysis, solution design, and solution design evaluation. The results of the research produced user requirements consisting of 6 user types, namely Catizen, Admin, Merch Seller, Treasurer, Content Manager, and Event Manager, with a total of 109 functional requirements. The result of the Prototype Application Testing using Usability Testing and UEQ Testing method. Usability Testing on the 6 actors resulted in an average of 95.34% in the effectiveness aspect, 0.25 goals/second in the Time Based Efficiency, and Based on the results of UEQ Testing, the Satisfaction aspect overall obtained an average score that falls into the good category, with Attractiveness scoring a Mean value of 1.67, Perpspicuty scoring a Mean value of 1.89, Efficiency scoring a Mean value of 1.53, Dependability scoring a Mean value of 1.53, Stimulation scoring a Mean value of 1.56, and Novelty scoring a Mean value of 1.22.